1980
DOI: 10.1111/j.1526-4610.1980.hed2004190.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in Patients Attending a Migraine Clinic: An Analysis by Computer of Age, Sex and Family History

Abstract: SYNOPSIS A survey is in progress of patients attending the Charing Cross Hospital Migraine Clinic in London. Information collected is stored for retrieval and analysis by computer. This paper reports some initial findings from patients seen during the first 212 years since the clinic opened. Patients registering with such a specialized clinic are not representative of the migraine population at large. Migraine sufferers present to the clinic at all ages from 6 to 70, but in three peaks, at 21–30, 41–45 and 51–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 1 publication
5
15
1
1
Order By: Relevance
“…Breslau and colleagues 15 studied migraine incidence in 1007 unselected individuals in the general population and reported a mean age at onset of any migraine of 13.7 years for men and 17.6 years for women. Steiner and colleagues 16 found that only 8% of 479 patients with migraine experienced onset after 40 years of age. Patients with migrainelike headaches occurring for the first time after 40 years of age deserve particular diagnostic diligence to exclude other potential causes of headache.…”
Section: Migraine Headachesmentioning
confidence: 99%
“…Breslau and colleagues 15 studied migraine incidence in 1007 unselected individuals in the general population and reported a mean age at onset of any migraine of 13.7 years for men and 17.6 years for women. Steiner and colleagues 16 found that only 8% of 479 patients with migraine experienced onset after 40 years of age. Patients with migrainelike headaches occurring for the first time after 40 years of age deserve particular diagnostic diligence to exclude other potential causes of headache.…”
Section: Migraine Headachesmentioning
confidence: 99%
“…Alguns autores, no entanto, encontraram este pico entre 20 e 29 anos 11,12 . Stewart e col. 10 acreditam que estes achados mais tardios se devem provavelmente a erros de memória dos pacientes.…”
Section: Discussionunclassified
“…A positive family history for migraine ascertained clinically was more frequently reported in cases with early onset as compared to late onset cases (Devoto et al, 1986;Steiner et al, 1980). In migraine with aura, there is evidence of multiple distributions of the age at migraine onset with peaks in late adolescence and after 30 years of age, respectively (Russell et al, 1996;Stewart et al, 1991).…”
Section: Genetic and Environmental Influences On Recurrent Headaches mentioning
confidence: 96%